Burden of Severe Illness Associated With Laboratory-Confirmed Influenza in Adults Aged 50–64 Years, 2010–2011 to 2016–2017. (27th December 2022) - Kim, Philip; Coleman, Brenda; Kwong, Jeffrey C; Plevneshi, Agron; Hassan, Kazi; Green, Karen; McNeil, Shelly A; Armstrong, Irene; Gold, Wayne L; Gubbay, Jonathan; Katz, Kevin; Kuster, Stefan P; et al.
Abstract: Background: Understanding the burden of influenza is necessary to optimize recommendations for influenza vaccination. We describe the epidemiology of severe influenza in 50- to 64-year-old residents of metropolitan Toronto and Peel region, Canada, over 7 influenza seasons. Methods: Prospective population-based surveillance for hospitalization associated with laboratory-confirmed influenza was conducted from September 2010 to August 2017. Conditions increasing risk of influenza complications were as defined by Canada's National Advisory Committee on Immunization. Age-specific prevalence of medical conditions was estimated using Ontario health administrative data. Population rates were estimated using Statistics Canada data. Results: Over 7 seasons, 1228 hospitalizations occurred in patients aged 50–64 years: 40% due to A(H3N2), 30% A(H1N1), and 22% influenza B. The average annual hospitalization rate was 15.6, 20.9, and 33.2 per 100 000 in patients aged 50–54, 55–59, and 60–64 years, respectively; average annual mortality was 0.9/100 000. Overall, 33% of patients had received current season influenza vaccine; 963 (86%) had ≥1 underlying condition increasing influenza complication risk. The most common underlying medical conditions were chronic lung disease (38%) and diabetes mellitus (31%); 25% of patients were immunocompromised. The average annual hospitalization rate was 6.1/100 000 in those without and 41/100 000 in those with any underlying condition, and highest in those with renal disease or immunocompromise (138 and 281 per 100 000, respectively). The case fatality rate in hospitalized patients was 4.4%; median length of stay was 4 days (interquartile range, 2–8 days). Conclusions: The burden of severe influenza in 50- to 64-year-olds remains significant despite our universal publicly funded vaccination program. These data may assist in improving estimates of the cost-effectiveness of new strategies to reduce this burden. Abstract : Despite a universal influenza vaccination program, average annual rates of influenza-associated hospitalization and mortality in adults aged 50–64 years were 22.4 and 0.9/100 000/year in our population. Incidence increased with age, and to a greater extent, in the presence of chronic comorbidities.